2012
DOI: 10.1038/nrm3461
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore complex composition: a new regulator of tissue-specific and developmental functions

Abstract: Nuclear pore complexes (NPCs) are multiprotein aqueous channels that penetrate the nuclear envelope connecting the nucleus and the cytoplasm. NPCs consist of multiple copies of roughly 30 different proteins known as nucleoporins (NUPs). Due to their essential role in controlling nucleocytoplasmic transport, NPCs have traditionally been considered as structures of ubiquitous composition. The overall structure of the NPC is indeed conserved in all cells, but new evidence suggests that the protein composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
265
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(273 citation statements)
references
References 187 publications
5
265
0
Order By: Relevance
“…In the absence of Nup98, along with the loss of RNAPII S5P, these antiviral genes are no longer efficiently induced, resulting in elevated levels of viral infection. This model is consistent with the recent results demonstrating recruitment of Nup98 to the promoter of developmentally regulated genes independent of transcription elongation, because Nup98 recruitment is insensitive to flavopiridol treatment (19), and that many developmental genes are known to be regulated at the level of pausing (8,37). Consistent with the hypothesis that Nup98 is a specific transcription activator, it also has been demonstrated that Nup98 interacts with histone-modifying enzymes CBP/p300 and histone deacetylases (45,46).…”
Section: Discussionsupporting
confidence: 79%
“…In the absence of Nup98, along with the loss of RNAPII S5P, these antiviral genes are no longer efficiently induced, resulting in elevated levels of viral infection. This model is consistent with the recent results demonstrating recruitment of Nup98 to the promoter of developmentally regulated genes independent of transcription elongation, because Nup98 recruitment is insensitive to flavopiridol treatment (19), and that many developmental genes are known to be regulated at the level of pausing (8,37). Consistent with the hypothesis that Nup98 is a specific transcription activator, it also has been demonstrated that Nup98 interacts with histone-modifying enzymes CBP/p300 and histone deacetylases (45,46).…”
Section: Discussionsupporting
confidence: 79%
“…Nuclear pore complexes (NPCs) are ∼100 MDa large multiprotein complexes that penetrate the NE to allow for regulated exchange of molecules between the nucleus and the cytoplasm (Raices and D'Angelo, 2012). They are composed of ∼30 different proteins called nucleoporins (Nups) that form the central part of NPC passing thorough the NE, with cytoplasmic filaments emanating towards the cytoplasm and the nuclear basket directed towards the nucleoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging evidence of heterogeneity within NPC composition between tissues, which is highlighted by the tissue-specific pathologies associated with loss of other NUPs. 14 It is thus possible that the NPC present within colonic smooth muscle is particularly susceptible to NUP35 depletion, leading to selective myopathy within this cell type. Regardless of the mechanism, the Nup35 F192L/F192L -mutant mouse phenotype has revealed a novel pathway involved in smooth muscle myopathy that may contribute to CIPO in humans.…”
Section: Nup35 and Colonic Myopathymentioning
confidence: 99%
“…NUP35 (also called NUP53) is part of the multiprotein nuclear pore complex (NPC), which is composed of multiple copies of approximately 30 different NUP proteins forming a complex >40 MDa in size. 14 The NPC plays a crucial role in allowing diffusion of small molecules and controlled movement of larger factors in and out of the nucleus. Proper NPC formation is also important for normal nuclear morphology.…”
mentioning
confidence: 99%